Lipid oxidation in minced beef meat with added Krebs cycle substrates to stabilise colour. (15th November 2015) - Yi, G.; Grabež, V.; Bjelanovic, M.; Slinde, E.; Olsen, K.; Langsrud, O.; Phung, V.T.; Haug, A.; Oostindjer, M.; Egelandsdal, B.
Highlights: Glutamate, succinate and citrate were added to minced meat to stabilise colour. Glutamate and succinate increased lipid oxidation. Glutamate and succinate were metabolised in both high and low oxygen. Citrate only used in high oxygen was not metabolised. Abstract: Krebs cycle substrates (KCS) can stabilise the colour of packaged meat by oxygen reduction. This study tested whether this reduction releases reactive oxygen species that may lead to lipid oxidation in minced meat under two different storage conditions. KCS combinations of succinate and glutamate increased peroxide forming potential (PFP, 1.18–1.32 mmol peroxides/kg mince) and thiobarbituric acid reactive substances (TBARS, 0.30–0.38 mg malondialdehyde (MDA) equivalents/kg mince) under low oxygen storage conditions. Both succinate and glutamate were metabolised. Moreover, under high oxygen (75%) storage conditions, KCS combinations of glutamate, citrate and malate increased PFP (from 1.22 to 1.29 mmol peroxides/kg) and TBARS (from 0.37 to 0.40 mg MDA equivalents/kg mince). Only glutamate was metabolised. The KCS combinations that were added to stabilise colour were metabolised during storage, and acted as pro-oxidants that promoted lipid oxidation in both high and low oxygen conditions.